Carpentry and building construction - l. Feirer John (Mc Graw Hill, 1997)
Carpentry and Building Construction" is widely used for vocational building construction programs in secondary and post-secondary schools. The fifth edition has been completely updated and expanded, so you can be sure your teaching is technically correct and state of the art. This comprehensive text covers everything from print reading to painting.